2014
DOI: 10.1371/journal.pone.0086427
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Respiratory and Heart Rates from the Correntropy Spectral Density of the Photoplethysmogram

Abstract: The photoplethysmogram (PPG) obtained from pulse oximetry measures local variations of blood volume in tissues, reflecting the peripheral pulse modulated by heart activity, respiration and other physiological effects. We propose an algorithm based on the correntropy spectral density (CSD) as a novel way to estimate respiratory rate (RR) and heart rate (HR) from the PPG. Time-varying CSD, a technique particularly well-suited for modulated signal patterns, is applied to the PPG. The respiratory and cardiac frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
71
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 23 publications
(53 reference statements)
0
71
0
2
Order By: Relevance
“…Many algorithms have been developed for estimating RR from the ECG and PPG [10,12], but have not yet been widely adopted into clinical practice. In this case study we demonstrated the application of exemplary techniques to the ECG and PPG.…”
Section: Introductionmentioning
confidence: 99%
“…Many algorithms have been developed for estimating RR from the ECG and PPG [10,12], but have not yet been widely adopted into clinical practice. In this case study we demonstrated the application of exemplary techniques to the ECG and PPG.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there is an interest to use reduced and low-cost instrumentation with the added benefit of extracting various clinical features from one single measurement [3]- [5]. The electrocardiographic (ECG) signal contains not only information related to the cardiac activity but also to the respiration [4], [6].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, respiratory signals derived using feature-based analysis must usually be re-sampled onto an even grid prior to frequency-domain analysis (see Figure 6). Fourier analysis has been used to calculate the frequency spectra of respiratory signals, from which the RR can be estimated [8]. However, this technique does not perform well when RR is non-stationary across the window of data analysed.…”
Section: Estimation Of Respiratory Ratementioning
confidence: 99%